Quantifying water and energy linkages in irrigation: Experiences from Viet Nam - Asian Development Bank (Asian Development Bank, 2017)
This publication summarizes the results of a pilot study to quantify water and energy use in high-effciency irrigation systems in Viet Nam. While Asia has the world’s fastest-growing economy, 29 of 48 countries assessed by the Asian Water Development Outlook 2016 are water-insecure, posing a threat to the region’s continued growth. As economies develop, increasing demands will be placed on water for food and water for energy. In the irrigation subsector, energy is required for ground and surface water pumping, as well as for fueling on-farm irrigation technology and other farm machinery. Water and energy are intrinsically linked, yet there is limited information on quantifying energy use in irrigation systems. This publication summarizes the results of a pilot study to quantify water and energy use in high-effciency irrigation systems within drought-affected provinces in Viet Nam. The study and publication have been supported by the Water Financing Partnership Facility. The study was conducted by the International Food Policy Research Institute (IFPRI) with support from a Viet Nam-based consultant within a suitable area identified in the central highlands of Viet Nam. The study is linked to an ADB-financed project preparation technical assistance for Water Efficiency Improvement in Drought Affected Provinces (WEIDAP).